Nature and Necessity An Essay in Physical Ontology - Fisk, Milton (Indiana University Press, 1974)
Nature and Necessity: An Essay in Physical Ontology presents genuinely new solutions to some salient problems in metaphysics. Fisk provides a new argument, based on the notion of conditional probability, for the claim that induction presupposes necessary connections. After devising an ontology of physical individuals to provide an objective basis for necessary connections, he uses this ontology to solve problems about relations, action, time, capacities, and events.